(untitled) (Journal of responsible AI & ethics, 2026)
Artificial Intelligence (AI) has revolutionized various sectors, from healthcare and finance to retail and security, by enhancing efficiency and enabling advanced predictive capabilities. However, this rapid development has raised significant concerns regarding personal data privacy. AI algorithms rely heavily on large datasets, often containing sensitive personal information, which can lead to privacy breaches if not managed properly. The balance between leveraging AI for innovation and protecting individual privacy is a delicate one. This paper explores the ethical challenges surrounding AI and personal data and aims to strike a balance between data-driven innovation and privacy protection. The study reviews existing regulatory frameworks, data governance models, and privacy-preserving techniques in AI systems. Through case studies and empirical analysis, the paper discusses how organizations can align innovation with responsible data usage and how individuals’ privacy rights can be safeguarded. Furthermore, it addresses key areas of concern such as data anonymization, algorithmic transparency, and user consent. The paper concludes by offering recommendations for policymakers and AI practitioners on how to navigate the evolving landscape of data privacy in AI.